Examining the role of terrestrial lichen transplants in restoring woodland caribou winter habitat - Sean B. Rapai; Duncan McColl; Richard Troy McMullin (The Forestry Chronicle)
The development of habitat restoration techniques for restoring critical woodland caribou (Rangifer tarandus caribou) winter habitat will play an important role in meeting the management thresholds in woodland caribou recovery plans. The goal is to restore disturbed environments within critical winter habitat for the declining woodland caribou. Woodland caribou are diet specialists, utilizing lichen-rich habitat for forage during winter months. Cladonia sub-genus Cladina is the most frequently eaten species during this time. Herein, we provide: 1) A review of previously used methods for transplanting Cladonia sub-genus Cladina and their feasibility in restoring woodland caribou winter habitat; 2) A stepby- step protocol on how to carry out a terrestrial lichen transplant program (using Cladonia sub-genus Cladina and C. uncialis); and, 3) An evaluation of our protocol through the establishment of a case study in northern British Columbia. Our results indicate that transplanting C. sub-genus Cladina fragments is the most efficient technique for transplanting terrestrial lichen communities, but transplanting lichen ‘patches’ or ‘mats’ may also be effective.